Nitrate photolysis as major summer daytime sources of ambient HONO in Southeastern Coastal China - Ziying Chen; Feng Zhang; Lingling Xu; Ziyi Lin; Xiuwen Yong; Yuping Chen; Gaojie Chen; Xiaoting Ji; Xiaolong Fan; Lingjian Wang; Mengren Li; Jinsheng Chen (Atmospheric Research, 2026)

Exosomal TGFBI promotes malignant progression of melanoma by regulating the FN1 signaling pathway - Yongliang Ge; Jingya Qiao; Lingling Ju; Lin Chen; Songnian Gao (Tissue and Cell, 2026)

Broad-specificity antibody profiled by hapten prediction for immunoassay development of anilinopyrimidine fungicides - Shiqi Lin; Liqiang Liu; Yingyue Zhu; Shanshan Song; Hua Kuang; Chuanlai Xu; Lingling Guo (Food Chemistry, 2026)

In-situ interfacial C–S–Zn bonding in N/S co-doped hard carbon anchoring ZnS for durable and fast sodium storage - Lingling Liu; Chuanyue Yang; Tong Wang; Jingwen Sun; Xu Yao; Ning Sheng; Xiansen Tao; Lin Shi; Jingquan Sha (Chemical Engineering Journal, 2026)

Nanozyme-enabled antibacterial sponge hydrogel-based electronic skin for underwater tactile sensing and slip-direction recognition - Jinli Fu; Lingling Zhang; Jiahao Yuan; Zhenyu Li; Chang Yang; Chunhua Luo; Hechun Lin; Xiaodong Tang; Hui Peng (Chemical Engineering Journal, 2026)

Anthraquinone‑modulated oxygen disproportionation enables highly selective singlet oxygen generation for pollutant degradation - Yu Luo; Chenqi Lu; Chuang Xiao; Lin Ding; Mengyuan Zhao; Lingling Liu; Longshuai Zhang; Xibao Li; Fang Deng; Xubiao Luo; Jian-Ping Zou (Journal of Environmental Chemical Engineering, 2026)

Atmospheric gaseous HCl influenced by sea-land breeze circulation in a southeast Chinese coastal city - Xiaolong Fan; Lei Yao; Yee Jun Tham; Chen Yang; Yuping Chen; Huiwen Chen; Gaojie Chen; Ziyi Lin; Youwei Hong; Mengren Li; Lingling Xu; Jinsheng Chen (ENGINEERING Environment, 2026)

An innovative urban drainage network pipe diameter optimization method based on an enhanced genetic algorithm and multi-stage disaster mitigation model - Weichao Yang; Maomao Li; Lingling Bin; Xuelian Jiang; Hao Wang; Meifang Ren; Haoyang Liang; Xiangdong Liu; Lin Yan (Journal of Hydrology, 2026)

In vitro and in vivo evaluation of Bacillus amyloliquefaciens E35 as prophylactic agents against Singapore grouper iridovirus - Yanxia Gao; Lingling Deng; Yibing Wang; Lin Huang; Jieying Yu; Xiangmou Qin; Junxiang Lai; Ermeng Yu; Shuyuan Zhang; Ying Pan; Jiwei Xu; Qing Yu; et al. (Fish & Shellfish Immunology, 2026)

Self-assembling gardenia pectin gel for cholestatic liver injury: Dual mechanisms of hepatoprotection via PPARα activation and gut microbial modulation - Lanjia Ao; Yujie Li; Lingling Zheng; Xiaolin Chen; Haoyuan Zeng; Wen Miao; Shuxian Yang; Tingting Zhou; Na Li; Jian-Lin Wu (Carbohydrate Polymers, 2026)

Pollution characteristics and health effects of vehicle emissions particulate matter in undersea tunnel - Anqi Hou; Lingjun Li; Ziyi Lin; Mengren Li; Xiaolong Fan; Xiaohe Wu; Yanting Chen; Lingling Xu; Jinsheng Chen (Journal of Environmental Sciences, 2026)

A capillarity-engineered trilayer Janus pad-based food preservation system for directional exudate management and sustained oregano-oil delivery - Ru Li; Wanru Jin; Lin Wang; Lingling He; Xiaowei Li; Peng Wang (Chemical Engineering Journal, 2026)

Characterization of the ctgf Promoter from Nibea coibor and its Response to TGF-β1 During Collagen Synthesis in Swim Bladder Cells - Ailing Zou; Yuying Yuan; Lingling Zhu; Yu Zhang; Lanfei Xiao; Xiaobo Wen; Fan Lin (Marine Biotechnology, 2026)

Experimental study on dynamic characteristics of marine soft soil foundations under minute-level intermittent loads from subway trains - Wei Huang; Lingling Li; Xinyu Lu; Lin Guo; Xibin Li; Xuanji Liu (Ocean Engineering, 2026)

Effects of Water-Fertilizer-Tillage Management on NH₃ Volatilization and Nitrogen Deposition in a Typical South China Agricultural System - Xiaoming He; Lingling Bi; Tianyi Chen; Siqi Yang; Shujuan Zhang; Siyi Yang; Chaohui Chen; Xin Wu; Xingjian Yang; Xueming Lin; Yongtao Li; Zhen Zhang (Water, Air, & Soil Pollution, 2026)

An advanced multifunctional strategy - enabled triboelectric nanogenerator for efficient wind-energy harvesting - Bin Wang; Yan Gu; Yan Zhou; Yamei Liu; Ning Huang; Guangze Du; Xinyang Liu; Lingling Han; Huibo Zhao; Zhen Wang; Yingao Xue; Jieqiong Lin (Chemical Engineering Journal, 2026)

Magnesium Ions Promote the Apoptosis of Cervical Cancer Cells through the PI3K/AKT/FoxO1 Pathway - Qian Zhao; Wang Yang; Lingling Cao; Yating Chen; Wumuti Baheti; Chen Lin (Biological Trace Element Research, 2026)

The primary sources of ROx radicals in atmosphere: Oxidative capacity and self-purifying effect - Gaojie Chen; Ziyi Lin; Xiaoting Ji; Lingling Xu; Xiaolong Fan; Mengren Li; Youwei Hong; Jinsheng Chen (Journal of Environmental Sciences, 2026)

CHAPS-involved chitooligosaccharide glycosylation of ferritin cage for encapsulation of bioactive molecule by a mild process - Junrui Ma; Runxuan Chen; Chang Liu; Shiyu Lin; Chunkai Gu; Lingling Zhang; Ruge Cao; Fang Wang; Demei Meng; Shihao Sun; Yuyu Zhang; Rui Yang (Food Chemistry, 2025)

Hydrological connection restoration may contribute more than species selection to organic carbon stock accumulation in mangrove - Qijuan Cao; Yuting Yang; Yan Lin; Lingling Zhong; Yutong Jin; Yujia Tian; Yuxi Chen; Luojian Mo; Yisheng Peng (Estuarine, Coastal and Shelf Science, 2025)

Development of the Folic Acid-Coated Nanoparticles Based on Human Serum Albumin for the Targeting Delivery of Betulin - Shihua Fu; Zaiyi Luo; Xin Chen; Lingling Yang; Xingjie Du; Kexin Chai; Yujie Zhang; Zhongbing Liu; Pei Jing; Changguang Wang; Yan Lin; Ruilin Lu; et al. (Journal of Pharmaceutical Innovation, 2025)

Study on the remediation of uranium contaminated water by indigenous bacteria in tailing pond and the mechanism of mineralization and precipitation - Jinxiang Deng; Mengjie Li; Lingling Wu; Zhijun Zhang; Huaimiao Zheng; Lin Hu; Yakun Tian; Min Wang (Process Safety and Environmental Protection, 2025)

Bioinspired phosphorylated cellulose nanocrystals-based multi-crosslinked binder for enhanced stability and sustainability in silicon anodes - Lan Zhao; Fengcai Lin; Haijun Li; Lingling Qian; Yingshan Shi; Zhiyi Cao; Xuan Yang; Biao Huang; Beili Lu; Hanyang Liu; Lirong Tang (Carbohydrate Polymers, 2025)

Estimating primary production in the California Current System using machine learning methods - Zixu Ye; Lingling Jiang; Qianru Wang; Qiang Li; Lin Wang; Siwen Gao; Zhigang Jiang (Estuarine, Coastal and Shelf Science, 2025)

Synergistically modulating multiple polarizations of electrically insulating and thermally conductive SnO2@C hollow core–shell nanofasciculi for exceptional EM protection capabilities - Baoxin Fan; Junhao Ding; Shiyang Cai; Kang Fu; Xiangyang Liu; Lingling Lin; Zhenjie Yu; Guoxiu Tong; Wenhua Wu (Chemical Engineering Journal, 2025)

Provenance of the detrital deposits in the Daju Basin of the Jinsha River, China - Lingling Li; Weiming Liu; Xu Lin; Anna Yang; Xuemei Li; Zewen Yang; Huimin Zhao (Journal of Geographical Sciences, 2025)

Proteoglycans and glycosaminoglycans: critical regulators in angiogenesis, vasculogenesis, and vascularized tissue engineering - Binbin Lin; Tianyu Sun; Yiqi Feng; Hongyu Liu; Lingling Zhang; Buling Wu; Jingyi Wu (Angiogenesis, 2025)

Characterization and gelling properties of pectin extracted from Gardenia fruit - Xuan Wang; Tian Tian; Na Li; Lingling Zheng; Yuyao Wu; Wei Bian; Jian-Lin Wu; Tingting Zhou (Food Hydrocolloids, 2025)

Tree-ring dating of the construction of the Yinshan tomb in Shaoxing, Zhejiang Province: A preliminary study - Shiyuan Shi; Congcong Xiao; Zebin Li; Yongxiang Wang; Hui Wang; Zhansheng Niu; Hongyan Zhang; Pengyu Lin; Xinrui Liu; Lingling Lu; Jiangfeng Shi; Huayu Lu (Science China Earth Sciences, 2025)

Stair-Stepping metamaterial and the derived isolator for all-DOF vibrations with multi-payloads - Haifeng Ou; Jia Zeng; Minqing Lin; Yifan Wang; Yujun Zeng; Xi Fang; Lingling Hu (Engineering Structures, 2025)

Accuracy of real-time PCR for the detection of paratuberculosis in actual samples: A systematic review and meta-analysis - Tian Liu; Hanyu Lin; Lingling Zhu; D. Aaron Yang; Huochun Yao; Zihao Pan (Preventive Veterinary Medicine, 2025)

Differential microbial degradation of cross-linked Polythene by Aspergillus niger in space and on the ground - Shuyuan Zhang; Lei Dang; Weiliang Li; Qin Zhang; Kui Xiao; Tong Tong; Qianqian Liu; Lingling Ma; Nana Chen; Lantao Zhang; Yali Feng; Yan Song; et al. (Chemical Engineering Journal, 2025)

UUV Cluster Distributed Navigation Fusion Positioning Method with Information Geometry - Lingling Zhang; Shijiao Wu; Chengkai Tang; Hechen Lin (Journal of Marine Science and Engineering, 2025)
The development and utilization of marine resources by humanity are increasing rapidly, and a single unmanned underwater vehicle (UUV) is insufficient to meet the demands of ocean exploitation. Large-scale UUV swarms present a primary solution; however, challenges such as underwater mountain ranges and signal attenuation critically impact the real-time collaborative positioning and autonomous clustering abilities of these swarms, posing major issues for their practical application. To address these challenges, this paper proposes a UUV cluster distributed navigation fusion positioning method with information geometry (UCDFP). This method transforms the navigation data of individual UUVs into an information geometric probability model, thereby reducing the impact of temporal asynchrony-induced positioning errors. By integrating factor graph theory and utilizing ranging information between UUVs, a distributed collaborative fusion positioning architecture for UUV swarms is established, enabling seamless dispersion and regrouping. In experimental evaluations, the proposed method is compared with existing techniques concerning convergence speed and the capability of UUV swarms for autonomous dispersion and regrouping. The results indicate that the method proposed in this paper achieves faster convergence and higher positioning stability during the autonomous clustering of UUV swarms, marking a notable advancement in underwater vehicular technology.

Aflatoxin B1 exposure induces Alzheimer's disease like pathology by disrupting redox homeostasis and activating ferroptotic signals in C57BL/6 J mice - Jinxian Lin; Huihui Hong; Sicheng Liu; Zhengwei Liang; Qixue Zheng; Kun Luo; Jiayi Li; Zhulin Du; Jinping Yu; Lingling Yang; Ping Deng; Huifeng Pi; et al. (Science of The Total Environment, 2025)

Preparation of nitrogen-doped biocarbon from sewage sludge and pine sawdust for superior hydrogen sulfide removal: Experimental and DFT studies - Kai Li; Xiaojun Niu; Lingling Zhou; Yukai Zheng; Zhenrong Lin; Minru Liu (Environmental Research, 2025)

Vertical distribution of microplastics in coastal sediments of Xuwen Coral Reef National Nature Reserve, China - Mayakrishnan Machendiranathan; Guangzhe Jin; Huaxia Huang; Tingbang Liang; Zongxuan Lin; Huiying Lin; Lingling Xie; Fajin Chen (Journal of Oceanology and Limnology, 2025)

The development of thickened fermented rice milk formulation for people with dysphagia: A view of multiple in vitro simulation methods - Zexue Lin; Lingling Ma; Bowen Li; Siming Zhao; Binjia Zhang (Food Research International, 2025)

A sustainable process for Pb, Zn, and Fe from copper slag by salt roasting-magnetization roasting-magnetic separation - Xinze Gao; Yinhe Lin; Dong Guan; Zhaohua Liu; Bo Deng; Qingshan Du; Yanjun Liu; Sen Yu; Juncheng Li; Lingling Cao (Process Safety and Environmental Protection, 2025)

Priority sources identification and risks assessment of heavy metal(loid)s in agricultural soils of a typical antimony mining watershed - Lianhua Liu; You Li; Xiang Gu; Roberto Xavier Supe Tulcan; Lingling Yan; Chunye Lin; Junting Pan (Journal of Environmental Sciences, 2025)

Lead-free halide perovskite-based optoelectronic synapse for reservoir computing - Lingling Zhang; Yafei Chen; Shuaifei Mao; Zhenyu Li; Chunli Jiang; Chunhua Luo; Hechun Lin; Jadranka Travas-Sejdic; Hui Peng (Chemical Engineering Journal, 2025)

Methods for detecting green tide in the Yellow Sea using Google Earth Engine platform - Yuhao Shang; Lingling Jiang; Lin Wang; Zixu Ye; Siwen Gao; Xiaohui Tang (Regional Studies in Marine Science, 2024)

The role of mitochondrial dysfunction in the association between trace metals and QTc prolongation in the aged population - Jiahui Wang; Peiyi Liu; Yankui Lin; Xia Zhang; Lingling Lin; Fengqi Wu; Ying Fu; Desheng Wu; Xiaohu Ren; Haiyan Huang; Xifei Yang; Jianjun Liu (Science of The Total Environment, 2024)

The joint impact of PM2.5 constituents on the risk of cerebrovascular diseases hospitalization: A large community-based cohort study - Shirui Chen; Yuqin Zhang; Ziqiang Lin; Ruqing Liu; Lingling Zheng; Xiuyuan Chen; Shao Lin; Yanji Qu; Chun Hao; Hui Tang; Jing Wei; Wangjian Zhang; et al. (Environmental Research, 2024)

Preparation of polyethylene based composite nanofiltration membrane and its application in removal of heavy metals for water purification - Lin Wang; Guiru Zhu; Haochen Ge; Yunbo Tong; Lingling Li; Ziqi Wang; Congjie Gao (Desalination, 2024)

Pestalotiopsis kenyana causes leaf spot disease on Rhododendron agastum in China - Xiaoli Li; Lingling Liu; Huie Li; Jianjun Lin; Yingping Zuo; Lijuan Peng; Haixia Ding (Crop Protection, 2024)

c-Jun N-terminal kinase 1/P53 signaling mediates intrinsic apoptosis of largemouth bass (Micropterus salmoides) hepatocytes under heat stress - Zijie Lin; Zhiying Cai; Lingling Li; Yekai Wei; Qufei Ling (Science of The Total Environment, 2024)

Unveiling the versatile performance of transition metal sulfides in peroxymonosulfate activation - Zhifang Zhao; Lin Lin; Shanshan Liu; Yiqian Chen; Sanford V. Daniels; Zijian Xu; Zhenhua Chen; Haitao Li; Yanqing Wu; Lingling Guo; Qiteng Zheng; Zhenhua Duan; et al. (Chemical Engineering Journal, 2024)

Annexin-A1 tripeptide enhances functional recovery and mitigates brain damage in traumatic brain injury by inhibiting neuroinflammation and preventing ANXA1 nuclear translocation in mice - Kai Lin; Yuejiao Hou; Ruxin Li; Fengyan Fan; Yinan Hao; Yuan Wang; Yue Huang; Peng Li; Lingling Zhu; Xin Huang; Yong-Qi Zhao (Metabolic Brain Disease, 2024)

Sealing solid agar in serum bottles for rapid isolation and long-term preservation of chemoautotrophic ammonia-oxidizing bacteria - Jiajie Wu; Manjun Zhan; Lingling Yuan; Yueyue Zhu; Weitie Lin; Jianfei Luo (Water Research, 2024)

Redistribution and activation of inert N-configuration in metallic electron donor towards boosted oxygen reaction kinetics for zinc-air batteries - Yiyao Cao; Yakai Chen; Ke Chen; Lingling Sun; Wenhao Si; Yan Yan; Huijuan Lin; Jixin Zhu; Peilei He; Yan Lu; Haijiao Xie; Kun Rui (Chemical Engineering Journal, 2024)

Photoelectric synaptic device based on Cu2ZnSnS4/ZnO heterojunction for non-volatile vision memory - Shuaifei Mao; Jiantong Ge; Lingling Zhang; Yannan Dai; Sheng Jiang; Yafei Chen; Chunli Jiang; Chunhua Luo; Bobo Tian; Hechun Lin; Hui Peng; Chun-Gang Duan (Chemical Engineering Journal, 2024)

Retrieval and spatiotemporal variation of total suspended matter concentration using a MODIS-derived hue angle in the coastal waters of Qinhuangdao, China - Lin Wang; Xiang Wang; Qinghui Meng; Yanlong Chen; Xinxin Wang; Lingling Jiang; Yuhao Shang (Frontiers in Marine Science, 2024)
The CIE hue angle has significant potential in marine ecology and environment monitoring using remote sensing methods. It is calculated from the remote sensing reflectance ( R rs ) of all visible bands, which serves as a comprehensive indicator of seawater radiance information and represents one of the key quantitative parameters for assessing seawater color. In this study, a remote sensing retrieval model of total suspended matter concentration (TSM) was developed using the in situ measured data acquired in the coastal waters of Qinhuangdao from 2013 to 2021. This model, based on the CIE hue angle, achieved performance metrics of R 2 = 0.68, MAPE=24.47%, and RMSE=2.72 mg/L, demonstrating better accuracy than traditional empirical models that utilize fewer bands. Based on this model, the monthly and interannual TSM in the coastal waters of Qinhuangdao from 2003 to 2023 were retrieved. Influenced by natural factors, such as the monsoons, the TSM in the coastal waters of Qinhuangdao generally exhibited a trend of first decreasing and then increasing from January to December. Except for certain anomalous years (2007, 2008, 2017, etc.), the overall variation process of TSM from 2003 to 2023 showed an initial increase followed by a decrease, closely related to the pollution reduction management requirements implemented by the Chinese government in different periods. The findings of this paper demonstrate that the coastal waters of Qinhuangdao have become clearer, and the ecological environment has been effectively improved as a result of the Chinese government’s vigorous promotion of ecological civilization construction, adhering to the development concept that ‘lucid waters and lush mountains are invaluable assets’, and by introducing the action plan for the comprehensive treatment of pollution in the Bohai Sea.

Exploring the effect of high pressure in the denaturation of casein micelles by in-situ SERS - Zhenhong Zheng; Han Lu; Yingfeng Lin; Lingling Shui; Mingliang Jin; Zhuo Jiang (Food Chemistry, 2024)

Inhibitory effect of malonic acid on Microcystis aeruginosa: Cell morphology, oxidative stress and gene expression - Chunyang Tao; Xiaojun Niu; Dongqing Zhang; Yuejin Liu; Lingling Zhou; Yunhao Han; Yujing Mo; Kaixin Wu; Yu Lin; Zhang Lin (Algal Research, 2024)

Severe nitrogen leaching and marked decline of nitrogen cycle-related genes during the cultivation of apple orchard on barren mountain - Yuwen Shen; Haining Chen; Haitao Lin; Ping Liu; Xiaozong Song; Yanan Ma; Mingli Li; Wensheng Gao; Lingling Song (Agriculture, Ecosystems & Environment, 2024)

Recent advances in swine wastewater treatment technologies for resource recovery: A comprehensive review - Lingling Zhou; Ming Liang; Dongqing Zhang; Xiaojun Niu; Kai Li; Zitao Lin; Xiaojun Luo; Yuying Huang (Science of The Total Environment, 2024)

Photochemical pollution during summertime in a coastal city of Southeast China: Ozone formation and influencing factors - Gaojie Chen; Xiaoting Ji; Jinsheng Chen; Lingling Xu; Baoye Hu; Ziyi Lin; Xiaolong Fan; Mengren Li; Youwei Hong; Jinfang Chen (Atmospheric Research, 2024)

Insight into an efficient microalgae co-culture system for biogas slurry treatment: Nutrients recovery and valuable biomass production - Lingling Zhou; Xiaojun Niu; Dongqing Zhang; Chunyang Tao; Yuejin Liu; Kai Li; Lin Zitao; Yongxin Liu; Yu Lin (Journal of Water Process Engineering, 2024)

Sources appointment and health risks of PM2.5-bound trace elements in a coastal city of southeastern China - Ziyi Lin; Xiaolong Fan; Gaojie Chen; Youwei Hong; Mengren Li; Lingling Xu; Baoye Hu; Chen Yang; Yanting Chen; Zhiqian Shao; Jinsheng Chen (Journal of Environmental Sciences, 2024)

The spatial transcriptomic landscape of human gingiva in health and periodontitis - Zongshan Shen; Ran Zhang; Yunjia Huang; Jiayao Chen; Mengjun Yu; Chunhua Li; Yong Zhang; Lingling Chen; Xin Huang; Jichen Yang; Zhengmei Lin; Songlin Wang; et al. (Science China Life Sciences, 2024)

Saliva-based detection of SARS-CoV-2: a bibliometric analysis of global research - Chun Zhou; Zhaopin Cai; Boxing Jin; Huisong Lin; Lingling Xu; Zhigang Jin (Molecular and Cellular Biochemistry, 2024)
Saliva has emerged as a promising noninvasive biofluid for the diagnosis of oral and systemic diseases, including viral infections. During the coronavirus disease 2019 (COVID-19) pandemic, a growing number of studies focused on saliva-based detection of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Taking advantage of the WoS core collection (WoSCC) and CiteSpace, we retrieved 1021 articles related to saliva-based detection of SARS-CoV-2 and conducted a comprehensive bibliometric analysis. We analyzed countries, institutions, authors, cited authors, and cited journals to summarize their contribution and influence and analyzed keywords to explore research hotspots and trends. From 2020 to 2021, research focused on viral transmission via saliva and verification of saliva as a reliable specimen, whereas from 2021 to the present, the focus of research has switched to saliva-based biosensors for SARS-CoV-2 detection. By far, saliva has been verified as a reliable specimen for SARS-CoV-2 detection, although a standardized procedure for saliva sampling and processing is needed. Studies on saliva-based detection of SARS-CoV-2 will promote the development of saliva-based diagnostics and biosensors for viral detection. Collectively, our findings could provide valuable information to help scientists perceive the basic knowledge landscapes on saliva-based detection of SARS-CoV-2, the past and current research hotspots, and future opportunities.

Meteorological impacts on the unexpected ozone pollution in coastal cities of China during the unprecedented hot summer of 2022 - Xiaoting Ji; Gaojie Chen; Jinsheng Chen; Lingling Xu; Ziyi Lin; Keran Zhang; Xiaolong Fan; Mengren Li; Fuwang Zhang; Hong Wang; Zhi Huang; Youwei Hong (Science of The Total Environment, 2024)

Polynorepinephrine-regulated filler sulfonation toward interfacial reformation and conductive promotion of nanocomposite proton exchange membrane - Tong Huang; Xin Liu; Ruibin Ma; Yangyang Gao; Xiaomin Xu; Chengrun Yan; Yuchen Guo; Xiaoxu Li; Yanzhou Qin; Lingling Liu; Jiandang Xue; Huadong Huang; et al. (Chemical Engineering Journal, 2024)

Differential expression of miRNAs and mRNAs in the livers of largemouth bass Micropterus salmoides under heat stress - Xuqian Zhao; Zijie Lin; Caijuan Li; Hao Zhu; Lingling Li; Wenjia Mao; Qufei Ling (Journal of Oceanology and Limnology, 2024)

Parent and halogenated polycyclic aromatic hydrocarbons exposure in aluminum smelter workers: Serum levels, accumulation trends, and association with health indicators - Chuxuan Zhao; Xiaoling Guan; Qinghua Zhang; Lingling Meng; Wei Lin; Ruiqiang Yang; Yingming Li; Guibin Jiang (Science of The Total Environment, 2024)

Deep convolutional neural networks for aged microplastics identification by Fourier transform infrared spectra classification - Ganning Zeng; Yuan Ma; Mingming Du; Tiansheng Chen; Liangyu Lin; Mengzheng Dai; Hongwei Luo; Lingling Hu; Qian Zhou; Xiangliang Pan (Science of The Total Environment, 2024)

Intermittent hypoxia training effectively protects against cognitive decline caused by acute hypoxia exposure - Guangbo Zhang; Guochun Yang; Yanzhao Zhou; Zhengtao Cao; Ming Yin; Lin Ma; Ming Fan; Yong-Qi Zhao; Lingling Zhu (Pflügers Archiv - European Journal of Physiology, 2024)

Long-term exposure to polystyrene microplastics induces hepatotoxicity by altering lipid signatures in C57BL/6J mice - Jiawen Tao; Ping Deng; Min Lin; Chunhai Chen; Qinlong Ma; Lingling Yang; Wenjuan Zhang; Yan Luo; Siyu Chen; Huifeng Pi; Zhou Zhou; Zhengping Yu (Chemosphere, 2024)

Effective degradation of zearalenone by dye-decolorizing peroxidases from Pleurotus ostreatus and its metabolic pathway and toxicity analysis - Shuai Ding; Chen Lin; Qiuyun Xiao; Fa Feng; Junfeng Wang; Xing Zhang; Shengjing Yang; Lingling Li; Fei Li (Science of The Total Environment, 2024)

Overlooked fluorine deficiency in children of South and East China may be exacerbated by climate change: Evidence from the national assessment - Lingfeng Zhou; Weigang Liang; Yaobin Meng; Xiaoli Zhao; Fei Guo; Lingling Liu; Wenjing Li; Miaomiao Teng; Fanhao Song; Zhiqiang Cao; Yidong Mi; Qigen Lin; et al. (Journal of Cleaner Production, 2024)

Sedimentary provenance constraints on the Cretaceous to Cenozoic palaeogeography of the western margin of the Jianghan Basin, South China - Xu Lin; Jing Liu-Zeng; Marc Jolivet; Weiming Liu; Feng Cheng; Haijin Liu; Lingling Li; Jixin Chen; Chengwei Hu; Xiaokang Chen (Gondwana Research, 2024)

Photochemistry in the urban agglomeration along the coastline of southeastern China: Pollution mechanism and control implication - Gaojie Chen; Qiao Shi; Lingling Xu; Shaocai Yu; Ziyi Lin; Xiaoting Ji; Xiaolong Fan; Youwei Hong; Mengren Li; Fuwang Zhang; Jinfang Chen; Jinsheng Chen (Science of The Total Environment, 2023)

Synergistic modulation of neuroendocrine-inflammation pathway by microRNAs facilitates intertidal adaptation of molluscs - Hao Chen; Lin Wang; Lingling Wang; Huan Zhang; Hao Wang; Linsheng Song (Fish & Shellfish Immunology, 2023)

Chronic cadmium exposure induces Parkinson-like syndrome by eliciting sphingolipid disturbance and neuroinflammation in the midbrain of C57BL/6J mice - Yudong Xu; Huihui Hong; Xiqin Lin; Tong Tong; Jingjing Zhang; Haotian He; Lingling Yang; Gaofeng Mao; Rongrong Hao; Ping Deng; Zhengping Yu; Huifeng Pi; et al. (Environmental Pollution, 2023)

Nitrogen availability mediates soil organic carbon cycling in response to phosphorus supply: A global meta-analysis - Xianzhen Luo; Lingling Zhang; Yongbiao Lin; Dazhi Wen; Enqing Hou (Soil Biology and Biochemistry, 2023)

Cellulose supported and strengthened shear stiffening gel with enhanced impact-resistant performance - Zhen Zhang; Xiaoming Lin; Junyi Lin; Nana Liu; Bolin Wan; Xiong Fang; Lingling Shui; Yingzhan Li; Kam C. Tam; Jin Huang; Guofu Zhou (Chemical Engineering Journal, 2023)

The intricate relationship between autoimmunity disease and neutrophils death patterns: a love-hate story - Ziwei Zhang; Lin Jin; Lianghu Liu; Mengqi Zhou; Xianzheng Zhang; Lingling Zhang (Apoptosis, 2023)

The immune enhancement effect of CpG-ODNs on the vaccine of inactivated Vibrio harveyi in tiger puffer (Takifugu rubripes) - Simiao Yu; Lei Gao; Zhen Geng; Wei Wu; Xuejie Lin; Ruijun Li; Shigen Ye; Lingling Wang; Linsheng Song (Aquaculture, 2023)

The effect of nitrous acid (HONO) on ozone formation during pollution episodes in southeastern China: Results from model improvement and mechanism insights - Baoye Hu; Gaojie Chen; Jinsheng Chen; Lingling Xu; Xiaolong Fan; Youwei Hong; Mengren Li; Ziyi Lin; Mingqiang Huang; Fuwang Zhang; Hong Wang (Science of The Total Environment, 2023)

Corrigendum to SaMT3 in Sedum alfredii drives Cd detoxification by chelation and ROS-scavenging via Cys residues [Environmental Pollution 315 (2022) 120410] - Jianqi Zhao; Ruohan Xie; Jiayu Lin; Lingling Xu; Xiaoyu Gao; Xianyong Lin; Shengke Tian; Lingli Lu (Environmental Pollution, 2023)

Potential causal links between long-term ambient particulate matter exposure and cerebrovascular mortality: Insights from a large cohort in southern China - Shirui Chen; Xiao Lin; Zhicheng Du; Yuqin Zhang; Lingling Zheng; Xu Ju; Tong Guo; Xinran Wang; Lichang Chen; Jie Jiang; Weihua Hu; Wangjian Zhang; et al. (Environmental Pollution, 2023)

Seasonal variation of aerosol optical properties in a coastal city of southeast China: Based on one year of measurements - Lingjun Li; Mengren Li; Siqing Zhang; Liqian Yin; Xiaoting Ji; Yuping Chen; Chao Dong; Lingling Xu; Xiaolong Fan; Gaojie Chen; Ziyi Lin; Youwei Hong; et al. (Atmospheric Environment, 2023)

Fe/Ni layered double hydroxide biocatalysts inhibit tumor growth through ROS and ferroptosis signaling pathway - Qiwen Pan; Fei Lin; Ruiqi Liu; Yilin Li; Xinyue Zhang; Rui Luo; Lingling Cai; Yang Liu; Wuguo Deng; Liru He (Chemical Engineering Journal, 2023)

Transcriptomics analysis reveals key lncRNAs and genes related to the infection of feline kidney cell line by panleukopenia virus - Lingling Zhang; Ruiying Liang; Abdul Raheem; Lin Liang; Xinglin Zhang; Shangjin Cui (Research in Veterinary Science, 2023)

A Strecker-like reaction triggering fluorescent sensing platform for enzyme-free and visual quantitative monitoring of carbamates - Lingling Qin; Jie Cao; Dan Lin; Shihao Xu; Yucheng Li; Changlong Jiang (Chemical Engineering Journal, 2023)

Lithiophilic interface dynamic engineering to inhibit Li dendrite growth for intrinsically safe Li-metal batteries - Tingting Jiang; Lingling Sun; Yao Zhang; Xiaomin Zhang; Huijuan Lin; Kun Rui; Jixin Zhu (Chemical Engineering Journal, 2023)

The shadows hang over immunotherapy-neutrophil extracellular traps in cancer - Dan Pu; Liyuan Yin; Xiaoqian Zhai; Ruoxiang Wang; Lin Huang; Qiang Wu; Lingling Zhu; Yuwen Zhou; Qinghua Zhou; Lu Li (Science China Life Sciences, 2023)

Single and combined effects of microplastics and cadmium on the sea cucumber Apostichopus japonicus - Chenxi Zhang; Chenggang Lin; Lingling Li; Mohamed Mohsen; Ting Wang; Xu Wang; Libin Zhang; Wei Huang (Marine Environmental Research, 2023)

The journey of prochloraz pesticide in Citrus sinensis: Residual distribution, impact on transcriptomic profiling and reduction by plasma-activated water - Qianwei Lin; Yuanwei Huang; Gangfeng Li; Zisheng Luo; Lei Wang; Dong Li; Yizhou Xiang; Lingling Liu; Zhaojun Ban; Li Li (Journal of Hazardous Materials, 2023)

Fabrication of polyamide thin film nanocomposite membranes with enhanced desalination performance modified by silica nanoparticles formed in-situ polymerization of tetramethoxysilane - Yunbo Tong; Yulin Wei; Han Zhang; Lin Wang; Lingling Li; Fangkun Xiao; Congjie Gao; Guiru Zhu (Journal of Environmental Chemical Engineering, 2023)

Biomass production and astaxanthin accumulation of Haematococcus pluvialis in large-scale outdoor culture based on year-round survey: Influencing factors and physiological response - Zhuoran Teng; Lingling Zheng; Zihan Yang; Lurong Li; Qi Zhang; Lin Li; Wei Chen; Gaohong Wang; Lirong Song (Algal Research, 2023)

RNA sequencing provides insights into the effect of dietary ingestion of microplastics and cadmium in the sea cucumber Apostichopus japonicus - Chenxi Zhang; Libin Zhang; Lingling Li; Mohamed Mohsen; Fang Su; Xu Wang; Chenggang Lin (Frontiers in Marine Science, 2023)
Introduction Microplastics (MPs) and cadmium (Cd) are persistent pollutants in aquatic environments. Sea cucumbers are susceptible to MPs and Cd due to their feeding behavior. Methods This study, based on Illumina sequencing, compared the transcriptomes of A. japonicus before and after Cd and/or MPs exposure. Additionally, we detected the changes of catalase (CAT), and superoxide dismutase (SOD) activity, glutathione (GSH), and malondialdehyde (MDA) content in sea cucumbers. Results and Discussion High concentration of MPs caused the increase of SOD activity. High concentration combined treatment resulted in significant up regulation of these four indicators in A. japonicus and had the largest number of differential expression genes (DEGs) reaching 1,618 DEGs, consisting of 789 up regulated along with 829 down regulated DEGs. Transcriptome results showed that Cd induced up regulation of intestinal FAS associated death domain protein (FADD) expression, which may cause apoptosis and inflammation. The increase of intestinal putative heparan sulfate 2-O-sulfotransferase in cadmium treatment groups provided a mechanism for host defense. The imbalance of expression of the NOD-like receptor (NLR) family inflammatory bodies and caspase 6 in the microplastic treatment group also led to the inflammatory reaction in the intestine of sea cucumber. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis showed that in the process of fatty acid metabolism, MPs and Cd showed antagonistic effects, mainly in the inconsistent expression of Stearoyl CoA Ddesaturase (SCD1) protein. The significant changes of Toll interacting protein (TOLLIP) and E-selectin (SELE) in all Cd and MPs treatment groups may indicate the key immune response genes of sea cucumber to Cd exposure and MPs exposure. These genes were involved in the immune defense of sea cucumber exposed to different levels of Cd and MPs. This study provided insights into the mechanism of dietary MPs and Cd intake in an economically and ecologically important invertebrate species.

Pollution mechanisms and photochemical effects of atmospheric HCHO in a coastal city of southeast China - Taotao Liu; Yiling Lin; Jinsheng Chen; Gaojie Chen; Chen Yang; Lingling Xu; Mengren Li; Xiaolong Fan; Fuwang Zhang; Youwei Hong (Science of The Total Environment, 2023)

Establishment of an efficient method for kiwifruit in vitro micrografting - Wantian Yao; Lingling Kong; Diya Lei; Bing Zhao; Honglan Tang; Xuan Zhou; Yuanxiu Lin; Yunting Zhang; Yan Wang; Wen He; Mengyao Li; Qing Chen; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Toxicity of single and combined 4-epianhydrotetracycline and cadmium at environmentally relevant concentrations on the zebrafish embryos (Danio rerio) - Yinxuan Lin; Jiao Yu; Meng Wang; Lingling Wu (Environmental Pollution, 2023)

Phthalocyanine-mediated interfacial self-assembly of magnetic graphene nanocomposites toward low-frequency electromagnetic wave absorption - Chenchen Liu; Shuning Liu; Xiaofang Feng; Ke Zhu; Guo Lin; Zhongxiang Bai; Lingling Wang; Xiaobo Liu (Chemical Engineering Journal, 2023)

Associations of metal profiles in blood with thyroiditis: a cross-sectional study - Yaosheng Luo; Huixian Zeng; Yanshi Ye; Genfeng Yu; Cheng Song; Siyang Liu; Xingying Chen; Yuqi Jiang; Hualin Duan; Yue Li; Shengqing He; Zhi Chen; et al. (Environmental Science and Pollution Research, 2022)
Autoimmune thyroiditis (AIT) is increasingly common, and serological markers include thyroid peroxidase antibody (TPOAb) and thyroglobulin antibody (TgAb). To determine if selected metals influence thyroiditis antibody positivity, this cross-sectional study investigated associations between metals and thyroiditis antibody status. Healthy individuals ( n = 1104) completed a questionnaire and underwent checkups of anthropometric parameters, thyroid function status, and levels of seven metals in blood (magnesium, iron, calcium, copper, zinc, manganese, and lead). Associated profiles of glyco- and lipid metabolism were also established. Logistic regression and restricted cubic spline (RCS) regression analysis were applied to adjudge associations between metals and TPOAb and TgAb status. It was found that, after adjusting for likely cofounding factors, participants with antibody positivity had significantly lower serum concentrations of magnesium and iron. When serum magnesium levels were analyzed in quartiles, the odds ratios of quartile 4 were 0.329–fold (95% confidence interval (CI): 0.167–0647) and 0.259-fold (95% CI 0.177–0.574) that of quartile 1 regarding TPOAb and TgAb positivity ( P = 0.004, 0.003). After adjustment, the RCS analysis detected nonlinear associations between iron and TPOAb and TgAb positivity ( P < 0.01, both). In stratified analyses, these associations regarding magnesium and iron remained for women of reproductive age, but not for postmenopausal women and men. We conclude that lower serum levels of magnesium and iron are associated with incremental positivity of thyroiditis antibodies and may be among the most important metals contributing to AIT in women of reproductive age.

Retraction Note: Water ecological environment changes in Southwest China based on GIS and environmental monitoring - Zheng Lingling; Peng Zhu; Haitao Lin (Arabian Journal of Geosciences, 2021)

RETRACTED ARTICLE:Water ecological environment changes in Southwest China based on GIS and environmental monitoring - Zheng Lingling; Peng Zhu; Haitao Lin (Arabian Journal of Geosciences, 2021)

Application of physiologically based pharmacokinetic modeling to predict the pharmacokinetics of telavancin in obesity with renal impairment - Wanhong Wu; Meng Ke; Lingling Ye; Cuihong Lin (European Journal of Clinical Pharmacology, 2021)

Fluorine enrichment of vegetables and soil around an abandoned aluminium plant and its risk to human health - Lingling He; Chenglong Tu; Shouyang He; Jiulai Long; Ya Sun; Yan Sun; Changhu Lin (Environmental Geochemistry and Health, 2021)

Ca2+/Calmodulin-NOS/NO-TNFs Pathway Hallmarks the Inflammation Response of Oyster During Aerial Exposure - Hao Chen; Lusheng Xin; Lin Wang; Huan Zhang; Rui Liu; Hao Wang; Xue Qiao; Lingling Wang; Linsheng Song (Frontiers in Marine Science, 2021)
Aerial exposure (emersion) due to the periodical ebb and flow of tides is a major stressor for intertidal organisms and a key environmental factor in shaping their local communities. Oysters are among the most emersion-tolerant mollusk species and can survive for several days under aerial exposure. Noticeably, overwhelming inflammation responses could occur during the emersion stress. However, mechanisms beneath the activation and modulation of emersion-induced inflammation response have remained largely unknown. Ca 2+ is an important intracellular second messenger that plays indispensable roles in inflammation response by cooperation with calmodulin (CaM) genes. Here, we showed that intracellular Ca 2+ accumulates rapidly in oyster hemocytes during emersion stress along with the changes in the protein levels of three CaM genes, which function as intracellular sensors of Ca 2+ . As downstream effector of Ca 2+ /CaM complex, nitric oxide synthase (NOS) activity in hemocytes was enhanced during the emersion stress, facilitating a greater production of nitrite oxide (NO). Augmentation of NO concentration was associated with the increased mRNA expression levels of two oyster cytokines (CgTNFs) during aerial exposure. The robust accumulation of cytokines and severe injury of tissues in oysters have been regarded as potential cause and marker of their death in prolonged emersion stress. Here, both the expression levels of CgTNFs and the tissue injuries of oysters were attenuated when Ca 2+ /CaM complex or NOS activity were repressed in vivo during the emersion stress. These findings indicate that Ca 2+ /CaM-NOS/NO-CgTNFs pathway is critically involved in the emersion-induced inflammation response in oysters and plays a role in the resistance against long-term aerial exposure.

Different effects of canopy and understory nitrogen addition on soil organic carbon and its related processes in a subtropical forest - Xiaofei Lu; Wendan Ren; Enqing Hou; Songbo Tang; Lingling Zhang; Zhanfeng Liu; Yongbiao Lin; Shenglei Fu; Dazhi Wen; Yuanwen Kuang (Journal of Soils and Sediments, 2021)

Analysis of sediment deposition in Lushui Reservoir to guide dredging - Hua Ge; Lingling Zhu; Qiusheng Lin; Chunyan Deng (Arabian Journal of Geosciences, 2021)

Molecular cloning and characterization of five genes from embryogenic callus in Miscanthus lutarioriparius - Lingling Zhao; Xiaofei Zeng; Xiaohu Hu; Jiajing Sheng; Fenglin Zhu; Lin Zhong; Fasong Zhou; Surong Jin; Zhongli Hu; Ying Diao (Acta Physiologiae Plantarum, 2020)
The regeneration from embryogenic callus of higher plants in tissue culture is regulated by explants types and developmental stage and also regulated by some genes. In Miscanthus lutarioriparius , five candidate genes were selected to decide the differential expression between embryogenic and non-embryogenic calli, including MlARF-GEP (guanine nucleotide-exchange protein of ADP ribosylation factor), MlKHCP (kinesin heavy chain like protein), MlSERK1 (somatic embryogenesis receptor-like kinases 1), MlSERK2 (somatic embryogenesis reportor-like kinases 2), and MlTypA (tyrosine phosphorylation protein A) with Genbank accession numbers KU640196–KU640200. Multiple sequence alignment analysis showed that five genes were highly conserved among members of their gene families respectively. Phylogenetic relationship analysis showed that five genes were closest with homologous genes of Zea mays and Sorghum . The qRT-PCR results showed significant differences of five genes expression pattern between two different callus types, the relative expression in embryogenic callus was detected to exceed in non-embryogenic callus. Furthermore, simple sequence repeats (SSR) marker statistics results via Chi-square showed a significant correlation between MlSERK1 genotype and induction of embryogenic callus in M. lutarioriparius . This study may lay the foundation of the molecular mechanism on the embryogenic callus induction of M. lutarioriparius and perhaps provide some gist for further study on genetic manipulation.

Validation of MODIS ocean-colour products in the coastal waters of the Yellow Sea and East China Sea - Lingling Jiang; Xiangyu Guo; Lin Wang; Shubha Sathyendranath; Hayley Evers-King; Yanlong Chen; Bingnan Li (Acta Oceanologica Sinica, 2020)

Electroacupuncture inhibits visceral pain via adenosine receptors in mice with inflammatory bowel disease - Tengfei Hou; Hongchun Xiang; Lingling Yu; Wen Su; Yang Shu; Hongping Li; He Zhu; Lixue Lin; Xuefei Hu; Shangdong Liang; Hong Zhang; Man Li (Purinergic Signalling, 2019)

Site-specific regulation of transcriptional responses to cadmium stress in the hyperaccumulator, Sedum alfredii: based on stem parenchymal and vascular cells - Yan Hu; Lingling Xu; Shengke Tian; Lingli Lu; Xianyong Lin (Plant Molecular Biology, 2019)

Chlorophyll fluorescence extraction from water-leaving radiance of algae-containing water through polarization - Lin Wang; Zhongfeng Qiu; Huifang Pang; Yongjian Liu; Yanlong Chen; Lingling Jiang (Journal of Ocean University of China, 2017)

2-Methylisoborneol production characteristics of Pseudanabaena sp. FACHB 1277 isolated from Xionghe Reservoir, China - Ting Zhang; Lingling Zheng; Lin Li; Lirong Song (Journal of Applied Phycology, 2016)

Upregulated TRIM32 correlates with enhanced cell proliferation and poor prognosis in hepatocellular carcinoma - Xiaopeng Cui; Zhipeng Lin; Yuyan Chen; Xiaofei Mao; Wenkai Ni; Jinxia Liu; Huiling Zhou; Xiaohang Shan; Lingling Chen; Jiale Lv; Zhongyi Shen; Chengwei Duan; et al. (Molecular and Cellular Biochemistry, 2016)

lncRNA DANCR suppresses odontoblast-like differentiation of human dental pulp cells by inhibiting wnt/β-catenin pathway - Lingling Chen; Zhi Song; Shuheng Huang; Runfu Wang; Wei Qin; Jia Guo; Zhengmei Lin (Cell and Tissue Research, 2016)

Patterns of succession between bloom-forming cyanobacteria Aphanizomenon flos-aquae and Microcystis and related environmental factors in large, shallow Dianchi Lake, China - Yanlong Wu; Lin Li; Lingling Zheng; Gongyuan Dai; Haiyan Ma; Kun Shan; Huadong Wu; Qichao Zhou; Lirong Song (Hydrobiologia, 2016)

Increased osteogenesis in osteoporotic bone marrow stromal cells by overexpression of leptin - Baoyu Zheng; Jun Jiang; Kai Luo; Lingling Liu; Minkui Lin; Yulin Chen; Fuhua Yan (Cell and Tissue Research, 2015)

Fibroblast Growth Factor 4 Is Required but not Sufficient for the Astrocyte Dedifferentiation - Guo-Dong Feng; Bao-Rong He; Fan Lu; Lin-Hong Liu; Lingling Zhang; Bo Chen; Zu-Ping He; Ding-Jun Hao; Hao Yang (Molecular Neurobiology, 2014)

Endothelial progenitor cells as a possible component of stem cell niche to promote self-renewal of mesenchymal stem cells - Hongwei Zhang; Lingling Xian; Zhiyi Lin; Chaozhe Yang; Meng Zhang; Wenlei Feng; Xinyu Peng; Xueling Chen; Xiangwei Wu (Molecular and Cellular Biochemistry, 2014)

Short-term effects of meteorological factors on children hand, foot and mouth disease in Guangzhou, China - Chun Chen; Hualiang Lin; Xiaoquan Li; Lingling Lang; Xincai Xiao; Peng Ding; Peng He; Ying Zhang; Ming Wang; Qiyong Liu (International Journal of Biometeorology, 2014)

Backscattering properties of marine phytoplankton Prorocentrum micans - Lingling Jiang; Dongzhi Zhao; Lin Wang (International Journal of Remote Sensing, 2014)

Characterization of 62 polymorphic EST-SSR markers in the blood clam (Tegillarca granosa) and their cross-amplification in Scapharca subcrenata - Yinghui Dong; Hanhan Yao; Zhihua Lin; Lingling Zhang; Zhenmin Bao (Conservation Genetics Resources, 2012)

Inhibitory effect of Salicornia europaea on the marine alga Skeletonema costatum - Dan Jiang; LingFeng Huang; YongQing Lin; LingLing Nie; SuLian Lv; TingYun Kuang; YinXin Li (Science China Life Sciences, 2012)

cDNA cloning and characterization of a new member of the tumor necrosis factor receptor family gene from scallop, Chlamys farreri - Jianguo Su; Limei Qiu; Ling li; Lin Liu; Lingling Wang; Vinu S. Siva; Dahui Yu; Linsheng Song (Molecular Biology Reports, 2011)

Effects of sediment burial disturbance on seedling survival and growth of Suaeda salsa in the tidal wetland of the Yellow River estuary - Zhigao Sun; Xiaojie Mou; Guanghui Lin; Lingling Wang; Hongli Song; Huanhuan Jiang (Plant and Soil, 2010)